Asymptomatic Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection in a rehabilitation facility: evolution of the presence of nasopharyngeal SARS-CoV-2 and serological antibody responses. - Harris,BHL; Zuhair,M; Di,Giovannantonio M; Rosadas,C; Khan,M; Short,C-E; Thaventhiran,T; Quinlan,R; Taylor,A; Calvez,R; Taylor,GP; Tedder,RS; et al. (Journal of Infectious Diseases, 2021)
At the start of the UK coronavirus disease 2019 epidemic, this rare point prevalence study revealed that one-third of patients (15 of 45) in a London inpatient rehabilitation unit were found to be infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) but asymptomatic. We report on 8 patients in detail, including their clinical stability, the evolution of their nasopharyngeal viral reverse-transcription polymerase chain reaction (RT-PCR) burden, and their antibody levels over time, revealing the infection dynamics by RT-PCR and serology during the acute phase. Notably, a novel serological test for antibodies against the receptor binding domain of SARS-CoV-2 showed that 100% of our asymptomatic cohort remained seropositive 3-6 weeks after diagnosis.